Efficiency of NSAIDs in preventing prosthetic joint infections (PJIs): inhibition of Staphylococcus aureus biofilms by etoricoxib through down regulation of bacterial adhesion genes - Muhammad Musthafa Poyil; Gobianand Kuppannan; Mahmoud H. El-Bidawy; Abdullah Mohammed Radwan Arafah; Tahane Bashir Mohammeddeen Ahmed; Nesreen Alsanousi; Aliya Elamin Mohammed; Mamoun Abdul Wahab AlFaki; Alaa Azhari Mohamed Hamid; Nagat Siednamohammeddeen (Archives of Microbiology, 2026)

Seasonal fluctuations in the hypothalamic irisin and its correlation with the hypothalamic-pituitary-gonadal -axis activity in male rhesus monkeys (Macaca mulatta) - Muhammad Saqib; Amel Aftab; Ghulam Nabi; Muhammad Noman Khan; Hira Zubair; Fazal Wahab; Maha Abdullah Alwaili; Nawal Al-Hoshani; Muhammad Shahab (Journal of Comparative Physiology B, 2026)

Wave energy converters for mild and low sea states: Classification, design optimization, and performance assessment — A review - Aqeel Ahmed; Z. Nizamani; A.K. Muhammad; Akihiko Nakayama; Mohamed Mubarak Abdul Wahab (Ocean Engineering, 2026)

Erratum to “Charge transfer and redox synergetic in MoSe2-V2O5 heterojunctions: high-performance bifunctional electrocatalyst for efficient overall water splitting” [Fuel 428 (2027) 140571] - Ambreen Bashir; Muhammad Rafaqat; Chang-Feng Yan; Md A. Wahab; Muhammad Sufyan Naeem; Abdual Waheed Rabbni; Tauseef Munawar; Faisal Iqbal (Fuel, 2026)

Corrigendum to “Charge transfer and redox synergetic in MoSe2-V2O5 heterojunctions: high-performance bifunctional electrocatalyst for efficient overall water splitting” [Fuel 428 (2027) 140571] - Ambreen Bashir; Muhammad Rafaqat; Chang-Feng Yan; Md A. Wahab; Muhammad Sufyan Naeem; Abdul Waheed Rabbani; Tauseef Munawar; Faisal Iqbal (Fuel, 2026)

Trade adjusted carbon emissions and renewable energy electricity output: Evidence from method of moment quantile regression for N-11 economies - Maaz Amin; Salman Wahab; Bilal Ahmed; Muhammad Imran; Shahid Ali; Sakiru Adebola Solarin (Environment, Development and Sustainability, 2026)

The impact of green brand image and green perceived risk on green trust and green purchase intention: the moderating role consumption values - Bilal Ahmed; Salman Wahab; Muhammad Imran; Muhammad Imran; Nawaz Ali Shah; Shamsher Ali (Environment, Development and Sustainability, 2026)

Retraction notice to ‘A facile two-step hydrothermal preparation of 2D/2D heterostructure of Bi2WO6/WS2 for the efficient photodegradation of blue under sunlight’ [Environ. Res. 234 (2023) 116550] - Muhammad Fiaz; Manzar Sohail; Ayman Nafady; Geoffrey Will; Md A. Wahab (Environmental Research, 2026)

Integrated Assessment of Water Quality and Sediment Load Production in River and Lake Basins: A Comprehensive Analysis for Environmental Management and Community Health - Mohd Khairul Amri Kamarudin; Noorjima Abd Wahab; Mohd Ekhwan Toriman; Firdaus Muhammad-Sukki; Ahmad Shakir Mohd Saudi; Fazureen Azaman (Water, Air, & Soil Pollution, 2026)
River and lake basins can be regarded as primary water sources, providing communities with a variety of services, including food supplies, flora and fauna habitats, and household uses. To evaluate the state of the water quality, particularly in the lake basin, sedimentation issues and water quality status are considered. The Kenyir Lake Basin's health was tracked in this study using the Water Quality Index (WQI), JPS River Index (JRI), and Sediment Load (SL) production. Determining and analysing the trends in water quantity and quality throughout the Kenyir Lake Basin was the goal of this study. For the purpose of this study, samples were taken at 21 different locations around the lake basin in the wet (November), dry (September), and normal (July) seasons. Six WQI parameters, four JRI parameters, and three SL production parameters have been chosen. In the linear connection to forecast WQI, JRI, and SL, several important variables serve as inputs. The key parameters were identified for each index, such as pH, Dissolved Oxygen (DO), and ammoniacal nitrogen (NH₃-N) which were critical for the WQI; specific flow was essential for the JRI; and Total Suspended Solids (TSS) were important for the sediment load (SL) production analysis. Furthermore, the Hazard Quotient (HQ) was subsequently calculated to conduct a preliminary assessment of the potential health risks associated with metal exposure. The elements' HQ ingestion values were discovered to be in the following order: Arsenic (As) > Cadmium (Cd) > Copper (Cu) > Cobalt (Co) > Chromium (Cr) > Nickel (Ni) > Zinc (Zn) > Plumbum (Pb); all averaged HQ values were less than 1, suggesting that there was little to no health risk from the metals in question. Overall, the WQI results indicate that the basin's water quality is generally Class I to Class II, with WQI values of at least 60% across all sampling points. Linear relationship analysis identified DO as the most critical parameter influencing the WQI across all seasons (contributing up to 64.40% in the dry season), followed by ammoniacal nitrate (AN) and Biochemical Oxygen Demand (BOD). The human health risk assessment revealed that the non-carcinogenic risk from metal exposure (As, Cd, Cu, Co, Cr, Ni, Zn, Pb) was negligible, as all averaged HQ values were less than 1. However, the carcinogenic risks associated with exposure to As and Cr were identified as high. Although the water quality has not reached a critical threshold, unregulated anthropogenic activities pose a substantial and intensifying threat to the ecosystem and local communities. These findings necessitate a more systematic environmental management approach to mitigate future degradation. Apart from the river, anthropogenic activities such as sand mining, tourism, agriculture, and municipal wastewater treatment were assessed using secondary data obtained from land use records, environmental monitoring reports, and official discharge statistics. Analysis of these data revealed that such activities play a substantial role in contributing to the concentration of polluting elements in the river water. Although the current level of water quality and quantity degradation in the Kenyir Lake Basin has not yet reached a critical threshold, the potential adverse impacts on the ecosystem and local communities are likely to intensify if these anthropogenic pressures remain unregulated.

Quality assessment and authenticity evaluation of honey samples from local traders in Peshawar, Pakistan - Abdul Wahab; Muhammad Younus; Shehla Begum; Wahid Gul (Environmental Monitoring and Assessment, 2026)

Characterization and fungicidal sensitivity of Phytophthora species causing citrus gummosis in Pakistan - Hadeed Ahmad; Muhammad Wahab; Muhammad Atiq; Muhammad Usman; Muhammad Hamza Shahid; Muhammad Usman Ali; Owais Iqbal; Muhammad Luqman Aleem; Qurban Ali; Nasir Ahmed Rajput (Physiological and Molecular Plant Pathology, 2026)

Technological trends in rainwater harvesting for micro-hydropower: a scientometric review - S. N. F. Abdullah; M. K. A. Kamarudin; N. A. Wahab; N. Yaakub; A. S. Mohd Saudi; M. N. A. Rahman; S. Sunardi; F. Muhammad-Sukki; I. N. Ismail (International Journal of Energy and Water Resources, 2026)

Black carbon and its relationship with PM2.5 and NO2 in a high-traffic urban environment of Kuala Lumpur - Murnira Othman; Mohd Talib Latif; Haris Hafizal Abd. Hamid; Ethel Garcia; Muhammad Ikram A. Wahab; Santhyami Santhyami; Li Li (Urban Climate, 2026)

Intraspecific and interspecific variation of Salvadora species (S. oleoides Decne. and S. persica L.) along an aridity gradient in dryland ecosystems - Ummar Iqbal; Atta Hussain Sahir; Muhammad Sharif; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf; Sadaf Rafiq; Sana Abid (Trees, 2026)

Microstructural adaptations of snow bush (Aerva javanica (Burm.f.) Juss. Ex Schult.) in desert ecosystems - Sana Abid; Ummar Iqbal; Muhammad Sharif; Sadaf Rafiq; Aisha Sana; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf (The Science of Nature, 2026)

Native Plants as Living Sensors: Tracking Air Pollution in Industrial Zones - Muhammad Sharif; Ummar Iqbal; Abdul Wahab; Muhammad Yousuf; Mehboob Ahmad; Muhammad Sharjeel Arif (International Journal of Environmental Research, 2026)

Caffeoylquinic acid derivatives isolated from Tussilago farfara L. as potential anti-leishmanial agents; in vitro and in silico studies - Izaz Ahmad; Salar Hafez-Ghoran; Muhammad Yousuf; Humaira Zafar; Atia-tul- Wahab; Sammer Yousuf; Mushtaq Ahmad; Inam Gul; Bates Kudaibergenova; M. Iqbal Choudhary (Natural Product Research, 2026)

Unravelling the influence of light on inshore coral and sponge recruits and their substrate communities - Gerard Ricardo; Muhammad Azmi Abdul Wahab; Eduardo Arias; Lee Bastin; Christopher Brunner; Heidi M. Luter; Matthew Nitschke; Matt Salmon; Andrew Negri (Marine Pollution Bulletin, 2026)

Flavonolignans from Lannea acida A. Rich. as potential antileishmanial agents - Muhammad Aamer; Muhammad Kamran; Muhammad Yousuf; Kayode Muritala Salawu; Humaira Zafar; Atia-tul Wahab; M. Iqbal Choudhary; Farooq-Ahmad Khan; Yan Wang (Natural Product Research, 2025)

Investigating the taxonomic scope of Meliolales species–host relationships and geographic trend - Muhammad Binyamin Khan; Abdul Wahab; Sana; Sardar Ali; De-Ping Wei; Marasinghe Wadige Diana Sandamali; S. Hongsanan; Xiang-Yu Zeng; Muhammad Ishaq; Munazza Kiran; Ting Chi Wen (New Zealand Journal of Botany, 2025)

Effect of dietary proteins on mayonnaise techno-functionality and rheology: A review - Wahab Ali Khan; Muhammad Waseem; Iqra Yasmin; Syed Abdul Wadood; Aiza Qamar; Muhammad Rizwan Javed; Muhammad Saleem; Crossby Osei Tutu (Food and Humanity, 2025)

Investigating the Effect of Sn and Pt Doping and Co-doping on the Photocatalytic Efficiency of Zirconia for Degradation of Acid Yellow-76 - Mian Hussain Shah; Saima Sadiq; Umar Wahab; Inam Ullah; Sardar Hussain; Nasr Ullah; Safiullah Khan; Zaffar Iqbal; Muhammad Ismail; Aadil Nabi Chishti; Muhammad Sadiq (Water, Air, & Soil Pollution, 2025)

Phenotypic Characterization and Adaptability of Wild Sugarcane to Diverse Pedospheric and Atmospheric Conditions - Ummar Iqbal; Mehboob Ahmad; Muhammad Sharif; Abdul Wahab; Muhammad Yousuf; Sadaf Rafiq; Sana Abid (Tropical Plant Biology, 2025)

Harnessing traditional ethnoveterinary practices and medicinal plants for sustainable livestock health in arid rangelands - Shumaila Batool; Murad Muhammad; Minahal Fatima; Muhammad Waheed; Muqadas Batool; Mona F. A. Dawood; Abdul Wahab; Abdul Waheed; Khalid Abbas (Genetic Resources and Crop Evolution, 2025)

Insulin Quantification Through Electrochemical and Optical Aptasensors: A Review - Jia Qi Chong; Muhammad Faiz Md Shakhih; Bhuwaneswaran Vijayam; Citartan Marimuthu; Congo Tak Shing Ching; Asnida Abdul Wahab (Annals of Biomedical Engineering, 2025)

Prevalence in Relation to Risk Factors of Babesia Bigemina in Bovines of Punjab (Pakistan) - Muhammad Wahab; Mian Abdul Hafeez; Faiza Aslam; Rimsha Farooq; Syeda Anam Sarwar; Waqas Ahmad; Liaqat Ali; Adeel Sattar; Waseem Khan (Acta Parasitologica, 2025)

Hemisynthesis of lupeol and betulin derivatives and their in vitro antimalarial activity against Plasmodium falciparum FCR3 - Ibrahim Dankane Bafarawa; Muhammad Solehin Abd Ghani; Arba Pramundita Ramadani; Shofiatul Fuadah; Muhammad Bisyrul Hafi Othman; Mohammad Nasir Ibrahim; Sook Yee Liew; Mohammad Tasyriq Che Omar; Habibah A. Wahab; Mohamad Nurul Azmi (Natural Product Research, 2025)

Evaluating soil health and aggregation potential in dryland soils under diverse land uses in semiarid Pakistan - Abdul Wahab; Kashif Ali Kubar; Muhammad Shaaban; Zia-ul-hassan; Inayatullah Rajpar; Allah Wadhayo Gandahi; Saleem Maseeh Bhatti; Muhammad Afzal Chhajro; Qambar Baloch (Environmental Monitoring and Assessment, 2025)

Plant root-mediated carbon sequestration and nutrient cycling in grassland ecosystems under land use and climate change - Abdul Waheed; Xu Qiao; Murad Muhammad; Yeernazhaer Yiremaikebayi; Xie Yingying; Hailiang Xu; Aishajiang Aili; Abdul Wahab (Agriculture, Ecosystems & Environment, 2025)

Efficient and sustainable transfer hydrogenation and N-formylation of nitroarenes using a facilely synthesized Co₄N/NC nanocatalyst - Anosha Rubab; Md A. Wahab; Ahmed Abdala; Muhammad Sharif; Waqas Ahmed; Manzar Sohail (Journal of Environmental Chemical Engineering, 2025)

Water security through next-generation surface-engineered membrane technologies for heavy metal removal - Muhammad Syafiq Alias; Wei Lun Ang; Abdul Wahab Mohammad (Journal of Environmental Chemical Engineering, 2025)

From scorching sands to survival: adaptive tale of the genus Tribulus (T. longipetalus, T. terrestris and T. pentandrus) in desert ecosystem - Ummar Iqbal; Muhammad Sharif; Sana Abid; Sadaf Rafiq; Abdul Wahab (The Science of Nature, 2025)

Quantitative exploration and conservation of the medicinal plant resources used by the inhabitants of Northern Pakistan - Murad Muhammad; Abdul Waheed; Abdul Wahab; Nimrah Ameen; Ibad Ullah; Muhammad Majeed; Muhammad Waheed; Khalid Rehman Hakeem; Mona F. A. Dawood; Wen-Jun Li (Genetic Resources and Crop Evolution, 2025)

Environmental factors attributed on dissemination of antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs) through PM2.5 and PM10 - Nurul Tasha Zulkifle; Muhammad Ikram A Wahab; Hui-min Neoh; Siti Shahara Zulfakar (Aerobiologia, 2025)

Insights into the adsorption of ibuprofen onto polyethylene microplastics using molecular dynamic simulation - Muhammad Ikhwan Nizam; Nurfarwizah Adzuan Hafiz; Mohamed Syazwan Osman; Mohamad Syafiq Abdul Wahab; Lei Wang; Noor Fitrah Abu Bakar; Mohamed Hasaan Hussain; Nur Lina Syahirah Mustapa; Chongqing Wang (Journal of Environmental Management, 2025)

Eco-friendly removal of direct orange 26 dye using lignin-ZnO composite: Optimization and application - Amina Sajjad; Kiran Aftab; Zumaira Siddique; Mohammad Rizwan Khan; Moonis Ali Khan; Abida Kausar; Naushad Ahmad; Muhammad Ali Baig; Rizwan Wahab (Journal of Environmental Management, 2025)

Structural Traits Driving Water Hyacinth (Eichhornia crassipes) Aggressive Spread and Ecosystem Disruption - Ummar Iqbal; Abdul Wahab; Sadaf Rafiq; Sibgha Noreen; Sana Abid; Muhammad Sharif; Mehboob Ahmad; Muhammad Yousuf (Water, Air, & Soil Pollution, 2025)

Disaster risk assessment in Malaysia: current state, challenges, and future directions - Muhammad Wafiy Adli Ramli; Nor Eliza Alias; Zulfaqar Sa’adi; Yusrin Faiz Abdul Wahab; Azimah ABD Rahman (Natural Hazards, 2025)

First report of Curvularia hawaiiensis causing leaf spot disease of grape in Pakistan - Muhammad Usman Ali; Muhammad Wahab; Muhammad Atiq; Muhammad Usman; Owais Iqbal; Muhammad Hamza Furqan; Ahmad Nawaz; Hamza Tariq; Ghalib Ayaz Kachelo; Nasir Ahmed Rajput (Journal of Plant Pathology, 2025)

Highly sensitive electrochemical sensing of fipronil using a ZnO/Graphene@C-dots hybrid nanocomposite - La Ode Agus Salim; Paulina Taba; Muhammad Zakir; Muhammad Nurdin; Abdul Wahid Wahab; Dahlang Tahir; St. Fauziah; Akrajas Ali Umar (Environmental Nanotechnology, Monitoring & Management, 2025)

Mitigating the Greenhouse Gases Intensity and Improving Fine Rice Productivity with Coated Urea Fertilizers in Semi-Arid Conditions - Ayesha Mustafa; Imran Khan; Muhammad Umer Chattha; Hafiz Abdul Wahab; Faisal Nadeem; Rikza Awan; Uthman Balgith Algopishi; Mohamed Hashem; Muhammad Umair Hassan (Journal of Soil Science and Plant Nutrition, 2025)

Synergistic defect engineering and z-scheme heterojunction in ultrasonication assisted CuFe LDH and carbon vacancies modified g-C3N4 composite for electrocatalytic water splitting and photocatalytic dye degradation - Muhammad Usman; Khurram Imran Khan; Samia; Sidra Khalid; Faiq Saeed; Abdul Wahab; Muhammad Sajjad Asghar; Ahmad Althobaiti; Alsharef Mohammad; Haitao Dai (Journal of Water Process Engineering, 2025)

Comparative efficacy of pharmacologic interventions in ulcerative colitis: a network meta analysis - Atta Ullah Khan; Maria Ali; Muhammad Aamir Wahab (Inflammopharmacology, 2025)
Introduction Ulcerative colitis is chronic inflammatory condition affecting the colon, necessitating remission inducing therapeutic interventions. With the emergence of newer more advanced options, their relative effectiveness remains unclear. This network meta-analysis (NMA) will compare the effectiveness of presently available biologics and small molecules in achieving and maintaining remission among patients of moderate-to-severe ulcerative colitis as part of induction and maintenance therapy. Methods A systematic search was conducted up to 21st February 2025, including only phase 2b/3 or 3 randomized controlled trials. The primary outcome was induction and maintenance of clinical remission (Full Mayo Score (FMS) ≤ 2, with no individual subscore > 1). Secondary outcomes assessed were clinical response, endoscopic improvement (Mayo Endoscopic Score (MES) ≤ 1 either with or without friability) and steroid free remission. Results Across 22 studies (7,683 patients), upadacitinib had the highest likelihood of inducing clinical remission (99.08%), clinical response (97.44%) and endoscopic improvement (99.32%), followed by Infliximab and guselkumab following close by for specific outcomes. In maintenance of clinical remission and endoscopic improvement upadacitinib again ranked highest (95.60%) and (99.46%). Tofacitinib (92.43%) has the highest probability with upadacitinib (87.73%) following behind in achieving steroid free remission. Conclusion Upadacitinib displayed high efficacy across multiple outcomes in both induction and maintenance therapy with Infliximab, guselkumab, and filgotinib following closely behind. For achieving steroid free remission tofacitinib has the highest probability of doing so. Overall small molecules and selective IL-23 inhibitors seems promising alternative to older biologics though additional head-to-head trial are warranted along with more real-world data.

Insights into Wild Medicinal Plants: Assessing Mineral Profiles in the Ojhor Valley, Chitral, Pakistan - Muhammad Nauman Khan; Barkat Ullah; Alevcan Kaplan; Abdul Razzaq; Ghulam Jelani; Sana Wahab; Syed Nasar Shah; Nazima Wahid; Muhammad Adnan; Mohamed Farouk Elsadek; M. Ajmal Ali; Majid Iqbal (Biological Trace Element Research, 2025)

Role of plant growth-promoting rhizobacteria in sustainable agriculture: Addressing environmental and biological challenges - Abdul Wahab; Farwa Batool; Gholamreza Abdi; Murad Muhammad; Shahid Ullah; Wajid Zaman (Journal of Plant Physiology, 2025)

Evaluation of methoxyflavones as dengue NS2B–NS3 protease inhibitors: an in silico and in vitro studies - Nur Farhana Mustafa; Kian-Kai Cheng; Siti Aisyah Razali; Habibah A. Wahab; Nurul Hanim Salin; Iffah Izzati Zakaria; Muhammad Helmi Nadri (Molecular Diversity, 2025)

Thriving in extremes: Adaptability potential of desert cotton Aerva javanica to hyper-arid saline conditions - Ummar Iqbal; Sana Abid; Muhammad Sharif; Sadaf Rafiq; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf (Journal of Arid Environments, 2025)

Phytoremediation Capacity of Saltwort (Salsola imbricata Forssk.) Determined by Tissue Organization and Physio-biochemical traits under Arid Saline Environments - Ummar Iqbal; Muhammad Sharjeel Arif; Muhammad Sharif; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf; Sadaf Rafiq; Sana Abid (Water, Air, & Soil Pollution, 2025)

From pollutant to purifier: Leveraging plastic waste-derived activated carbon for sustainable water remediation solutions - Hammad Khan; Muhammad Usama; Mohammad Ilyas Khan; Fazal Wahab; Izhar Ahmad; Ali Hamid; Sajjad Hussain; Arslan Maqbool (Journal of Environmental Management, 2025)

Prevalence and genetic diversity of potato virus Y strains in Pakistani potato fields: insights from partial sequence analysis - Muhammad Hamza Shahid; Ghulam Mustafa Sahi; Zunaira Afzal Naveed; Safdar Ali; Muhammad Wahab; Muhammad Sagheer; Azher Mustafa (Journal of Plant Diseases and Protection, 2025)

Navigating Climate Change: Exploring the Dynamics Between Plant–Soil Microbiomes and Their Impact on Plant Growth and Productivity - Murad Muhammad; Abdul Wahab; Abdul Waheed; Khalid Rehman Hakeem; Heba Ibrahim Mohamed; Abdul Basit; Muhammad Danish Toor; Yong‐Hong Liu; Li Li; Wen‐Jun Li (Global Change Biology, 2025)
Understanding the intricate interplay between plant and soil microbiomes and their effects on plant growth and productivity is vital in a rapidly changing climate. This review explores the interconnected impacts of climate change on plant–soil microbiomes and their profound effects on agricultural productivity. The ongoing rise in global temperatures, shifting precipitation patterns and extreme weather events significantly affect the composition and function of microbial communities in the rhizosphere. Changes in microbial diversity and activity due to rising temperatures impact nutrient cycling, microbial enzyme synthesis, soil health and pest and disease management. These changes also influence the dynamics of soil microbe communities and their capability to promote plant health. As the climate changes, plants' adaptive capacity and microbial partners become increasingly crucial for sustaining agriculture. Mitigating the adverse effects of climate change on plant growth and agricultural productivity requires a comprehensive understanding of the interconnected mechanisms driving these processes. It highlights various strategies for mitigating and adapting to environmental challenges, including soil management, stress‐tolerant crops, cover cropping, sustainable land and water management, crop rotation, organic amendments and the development of climate‐resilient crop varieties. It emphasises the need for further exploration of plant–soil microbiomes within the broader context of climate change. Promising mitigation strategies, including precision agriculture and targeted microbiome modifications, offer valuable pathways for future research and practical implementation of global food security and climate change.

An in-depth investigation of the nutraceutical value and medicinal perspectives of wild medicinal plants in Ojhor Valley, Hindukush Range, Chitral, Pakistan - Muhammad Nauman Khan; Barkat Ullah; Alevcan Kaplan; Sana Wahab; Baber Ali; Sami Al Obaid; Mohammad Javed Ansari (Genetic Resources and Crop Evolution, 2025)

Renewable wind energy resources in offshore low wind speeds regions near the equator: A review - Z. Nizamani; A.K. Muhammad; Montasir Osman Ahmed Ali; Mubarak Abdul Wahab; A. Nakayama; Mirza Munir Ahmed (Ocean Engineering, 2024)

Performance evaluation of the monopile foundation using PISA methodology under extreme loading conditions in Malaysia - Ng Chee Cong; Z. Nizamani; Khalid Ahmed Fakhurddin; A.K. Muhammad; Mubarak Abdul Wahab (Ocean Engineering, 2024)

Smoothed particle hydrodynamics simulation of debris flow on deposition area - Muhammad Khairi A. Wahab; Mohd Remy Rozainy Mohd Arif Zainol; Jazaul Ikhsan; Mohd Hafiz Zawawi; Mohamad Aizat Abas; Norazian Mohamed Noor; Norizham Abdul Razak; Neeraj Bhardwaj; Siti Multazimah Mohamad Faudzi (Natural Hazards, 2024)

Exploring vortex dynamic efficiency in hydro-suction system: a combined experimental and numerical investigation - Mohammed Hamid Rasool; Mohd Remy Rozainy Mohd Arif Zainol; Norizham Abdul Razak; Muhammad Khairi A. Wahab; Neeraj Bhardwaj (Modeling Earth Systems and Environment, 2024)

The interplay of temperature, light, and substrate type in driving growth and reproduction of an important tropical crustose coralline alga - Jenny Fong; Timothy L. Jackson; Florita Flores; Elsa Antunes; Muhammad Azmi Abdul Wahab; Andrew P. Negri; Guillermo Diaz-Pulido (Journal of Applied Phycology, 2024)
Crustose coralline algae (CCA) from the genus Titanoderma are reported to induce high levels of coral larval settlement across a wide diversity of species. Consequently, Titanoderma is a promising taxon to cultivate in aquaculture facilities for application in coral reef restoration projects. However, knowledge on the optimum conditions to promote growth and reproduction in Titanoderma is limited. To investigate this, we cultured adult fragments of Titanoderma sp. at two temperatures (27.5 or 30 °C) and two light levels (mean maximum midday irradiance of 10 or 40 µmol photons m −2 s −1 ) on three different tile materials (CaCO 3 , concrete, or PVC). We found that the combination of 27.5 °C and 40 µmol photons m −2 s −1 were best for adult fragment growth. Greater number of conceptacles were formed under higher light intensities, while temperature did not have an influence. Sporeling settlement and subsequent growth into juveniles were only evident at 40 µmol photons m −2 s −1 , with substantially higher recruitment on substrates made of concrete. These results provide important insights for developing optimal conditions to cultivate Titanoderma sp. in aquaculture facilities to support reef restoration projects using sexually produced corals.

First report of Pythium aphanidermatum causing stem and root rot disease on sesame (Sesamum indicum L.) in Punjab, Pakistan - Nasir Ahmed Rajput; Muhammad Atiq; Abdul Mubeen Lodhi; Rehana Naz Syed; Owais Iqbal; Muhammad Usman Ali; Muhammad Wahab; Hadeed Ahmad (Journal of Plant Pathology, 2024)

Harnessing bacterial endophytes for environmental resilience and agricultural sustainability - Murad Muhammad; Abdul Wahab; Abdul Waheed; Heba Ibrahim Mohamed; Khalid Rehman Hakeem; Li Li; Wen-Jun Li (Journal of Environmental Management, 2024)

The AutoSpawner system - Automated ex situ spawning and fertilisation of corals for reef restoration - Andrea Severati; F. Mikaela Nordborg; Andrew Heyward; Muhammad A. Abdul Wahab; Christopher A. Brunner; Jose Montalvo-Proano; Andrew P. Negri (Journal of Environmental Management, 2024)

Effects of material type and surface roughness of settlement tiles on macroalgal colonisation and early coral recruitment success - Jenny Fong; Blake D. Ramsby; Florita Flores; Tewodros Dada; Elsa Antunes; Muhammad Azmi Abdul Wahab; Andrea Severati; Andrew P. Negri; Guillermo Diaz-Pulido (Coral Reefs, 2024)
Sexual propagation of corals is a promising strategy for coral restoration, but one of the main challenges is the high mortality of coral spat due to competitive interactions with macroalgae during the early life history stages. Optimising the properties of settlement substrates such as material types and surface roughness has the potential to improve the survival of spat by limiting the recruitment and growth of macroalgae. In this study, we assessed the effects of modifying surface roughness across three different tile materials (alumina-based ceramic, calcium carbonate (CaCO 3 ), and concrete) on the settlement success and post-settlement survivorship of Acropora kenti coral larvae in six mesocosm tanks, each with different established macroalgal communities. The macroalgal community compositions on the tiles were significantly different among material types, but not surface roughness, although the type and abundance of macroalgal species were heavily influenced by the established tank communities. Increasing surface roughness did not affect larval settlement success or spat survivorship. Substantially higher larval settlement density was found on concrete tiles (1.92 ± 0.10 larvae cm −2 ), but spat survival was the highest on CaCO 3 tiles (73.4 ± 4.2% survived). Very strong competitive interactions were observed between spat and macroalgae, with overgrowth by the crustose coralline alga Crustaphytum sp. and the brown alga Lobophora sp. being the primary cause of spat mortality. Overall, when taking into account both settlement and survival rates, concrete was the best performing among the tile types tested here.

Qualitative and quantitative analysis of high-value metabolites from callus culture of Alcea rosea L. - Hasnat Tariq; Anisa Andleeb; Sannia Batool; Urooj Ali; Muhammad Waqas; Abdul Wahab; Gouhar Zaman; Samantha Drouet; Nathalie Giglioli-Guivarc’h; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

The concentration of particulate matters in mechanically ventilated school classroom during haze episode in Kuala Lumpur City Centre - Azwani Alias; Mohd Shahrul Mohd Nadzir; Mohd Talib Latif; Md Firoz Khan; Haris Hafizal Abd Hamid; Mazrura Sahani; Muhammad Ikram A. Wahab; Murnira Othman; Faizal Mohamed; Noorlin Mohamad; Norhaniza Amil; Otuyo Muhsin Kolapo (Air Quality, Atmosphere & Health, 2024)

Agriculture and environmental management through nanotechnology: Eco-friendly nanomaterial synthesis for soil-plant systems, food safety, and sustainability - Abdul Wahab; Murad Muhammad; Shahid Ullah; Gholamreza Abdi; Ghulam Mujtaba Shah; Wajid Zaman; Asma Ayaz (Science of The Total Environment, 2024)

Assessing the impact of geopolitical, economic, and institutional factors on China's environmental management in the Russian-Ukraine conflicting era - Bilal Ahmed; Salman Wahab; Syed Rahim; Muhammad Imran; Afaq Ahmad Khan; Mohammed Moosa Ageli (Journal of Environmental Management, 2024)

Utilizing a Low-Cost Air Quality Sensor: Assessing Air Pollutant Concentrations and Risks Using Low-Cost Sensors in Selangor, Malaysia - Zaki Khaslan; Mohd Shahrul Mohd Nadzir; Hamimatunnisa Johar; Zhang Siqi; Nor Azura Sulong; Faizal Mohamed; Shubhankar Majumdar; Fatin Nur Afiqah Suris; Nor Syamimi Sufiera Limi Hawari; Jintu Borah; Maggie Ooi Chel Gee; Muhammad Ikram A. Wahab; et al. (Water, Air, & Soil Pollution, 2024)

Assessment of the microbial electrochemical sensor (SENTRY™) as a potential wastewater quality monitoring tool for common pollutants found in Malaysia - Muhammad Farhan Hil Me; Wei Lun Ang; Ahmad Razi Othman; Abdul Wahab Mohammad; Ahmad Afiq Arshad Nasharuddin; Alijah Mohd Aris; Bee Chin Khor; Swee Su Lim (Environmental Monitoring and Assessment, 2024)

Integration of chitosan coating and short-term hypobaric treatment extends postharvest life and upregulates defense-related enzymes in apple fruit - Syed Umair Shah; Majid S. Hashmi; Muhammad Rafiullah Khan; Ayaz Ahmad; Aysha Riaz; Yosef Al Shoffe; Said Wahab; Muhammad Ayub; Antonio Ippolito (European Journal of Plant Pathology, 2024)

Navigating environmental concerns: Unveiling the role of economic growth, trade, resources and institutional quality on greenhouse gas emissions in OECD countries - Salman Wahab; Muhammad Imran; Bilal Ahmed; Syed Rahim; Taimoor Hassan (Journal of Cleaner Production, 2024)

Unleashing the dye adsorption potential of polyaminoimide homopolymer: DFT, statistical physics, site energy and pore size distribution analyses - Nabeel Hussain; Hammad Khan; Sajjad Hussain; Muhammad Arshad; Muhammad Umar; Fazal Wahab (Journal of Environmental Chemical Engineering, 2023)

Sustainable wastewater purification with crab shell-derived biochar: Advanced machine learning modeling & experimental analysis - Amina Bibi; Hammad Khan; Sajjad Hussain; Muhammad Arshad; Fazal Wahab; Muhammad Usama; Khurram Khan; Feryal Akbal (Bioresource Technology, 2023)

Enhancement in photocatalytic selectivity of TiO2-based nano-catalyst through molecular imprinting technology - Abdul Wahab; Muhammad Ali Minhas; Huma Shaikh; Hua-Ming Xiao; Muhammad Imran Malik (Environmental Science and Pollution Research, 2023)

Multiple design and modelling approaches for the optimisation of carbon felt electro-Fenton treatment of dye laden wastewater - Hammad Khan; Sajjad Hussain; Muhammad Amad Ud Din; Muhammad Arshad; Fazal Wahab; Usman Hassan; Abad Khan (Chemosphere, 2023)

RETRACTED: A facile two-step hydrothermal preparation of 2D/2D heterostructure of Bi2WO6/WS2 for the efficient photodegradation of methylene blue under sunlight - Muhammad Fiaz; Manzar Sohail; Ayman Nafady; Geoffrey Will; Md A. Wahab (Environmental Research, 2023)

Deciphering genetic-by-environment interaction, pests and disease's reaction, grain quality, and response to fertilizer for targeting high-yielding rice varieties - Trias Sitaresmi; Nafisah Nafisah; Untung Susanto; Rahmini Rahmini; Yuni Widyastuti; Bram Kusbiantoro; Muhammad Ismail Wahab; Aris Hairmansis; Yudhistira Nugraha (Ecological Genetics and Genomics, 2023)

Interactions of Metal‐Based Engineered Nanoparticles with Plants: An Overview of the State of Current Knowledge, Research Progress, and Prospects - Abdul Wahab; Asma Munir; Muhammad Hamzah Saleem; Mukhtar Iderawumi AbdulRaheem; Humera Aziz; Manar Fawzi Bani Mfarrej; Gholamreza Abdi (Journal of Plant Growth Regulation, 2023)

Green financing strategy for low-carbon economy: The role of high-technology imports and institutional strengths in China - Taimoor Hassan; Yasir Khan; Adnan Safi; He Chaolin; Salman Wahab; Abdul Daud; Muhammad Tufail (Journal of Cleaner Production, 2023)

Secondary metabolites from the stem bark of Stereospermum acuminatissimum and their antimicrobial activity - Peron Bosco Leutcha; Jean-Bosco Jouda; Virginie Flaure Tsague Tankeu; Larissa Mekontso Magnibou; Atia-tul-Wahab; Muhammad Iqbal Choudhry; Alain Meli Lannang (Biochemical Systematics and Ecology, 2023)

The impact of climate change on agricultural productivity and agricultural loan recovery; evidence from a developing economy - Fakhrul Wahab; Majid Jamal Khan; Muhammad Yar Khan; Rukhshanda Mushtaq (Environment, Development and Sustainability, 2023)

Economic and non-economic drivers of tourism: bidirectional causality of tourism and environment for South Asian economies - Salman Wahab; Bilal Ahmed; Muhammad Imran; Adnan Safi; Zeeshan Wahab (Environmental Science and Pollution Research, 2023)

Entropy-based grid approach for handling outliers: a case study to environmental monitoring data - Anwar Shah; Bahar Ali; Fazal Wahab; Inam Ullah; Kassian T. T. Amesho; Muhammad Shafiq (Environmental Science and Pollution Research, 2023)

Local ecological knowledge can support improved management of small-scale fisheries in the Bay of Bengal - Hadayet Ullah; Md Abdul Wahab; Md Jalilur Rahman; Shaheed Nasrullah Al Mamun; Uttam Kumar; Muhammad Arifur Rahman; Sazeed Mehrab Souhardya; Ilias Ebne Kabir; Monayem Hussain; Md. Bokthier Rahman; Sk Md Saeef Ul Hoque Chishty (Frontiers in Marine Science, 2023)
Fishers’ local ecological knowledge (LEK) can be used to reconstruct or supplement long-term trends in heavily exploited population or poorly assessed species with low biomass. We used historical memories of small-scale fishers to understand their perceptions of changes in catch trends in marine fisheries over the last 20 years. The study aimed at evaluating how fishers could provide consistent and reliable data on major fish species/groups comparable with official catch data and to explore the potential of increasing their participation in fishery management. We conducted focus group discussions (FGDs) and key informant interviews with experienced fishers and stakeholders, using a structured template related to the catch and effort data. Using FGD data, we systematically compared changes in fish catch rates and effort over time and space. Data were collected on major groups of species that had reasonable landing over time. Overall, the analysis revealed changes in catch rate, monthly landings per landing center, factors that likely influence the catch trends, and the spatial expansion of fisheries. Our study provides insight into species’ abundance over time. Fishers’ LEK shows declining catch rates for major species and groups, but monthly harvests at landing centers have increased over two decades because of increased fishing efforts. Small-scale fishers are catching more fish from deeper waters over time, indicating a geographical expansion and/or development of fisheries beyond traditionally exploited areas. Such expansions of nearshore fisheries may result from the overfishing of nearby areas. On the contrary, this could be viewed as a positive indication of the potential for growth and development of small-scale fisheries in the region, especially in the context of the blue economy. The agreement between official statistics and fishers’ data on species catch trends over time suggests that fishers have a good understanding of their fishing system. This indicates that fishers’ knowledge could be invaluable, especially in data-poor areas. LEK integration into policy and management is thus expected to facilitate the efficient management of small-scale fisheries.

Effect of dietary inclusion of mealworm frass on growth, hematology, and serum biochemistry of sheep - Muhammad Ayaz; Rajwali Khan; Sarzamin Khan; Syed Muhammad Suhail; Khalid Khan; Ijaz Ahmad; Abdul Wahab; Amel Ayari-Akkari; Gehan Othman (Tropical Animal Health and Production, 2023)

Cryptic biodiversity inhabiting coral reef sponges - Anita M. George; Dave Abdo; Muhammad Azmi Abdul Wahab; Merrick Ekins; John N. A. Hooper; Steve Whalan (Marine Ecology, 2023)
Sponges host a wide range of cryptic biodiversity both internally and externally. This study quantified the biodiversity inhabiting, or associated with, three morphologically distinct coral reef sponges. Coelocarteria singaporensis , Coscinoderma mathewsi and Ircinia microconulosa were collected from fringing reefs at Orpheus Island, central Great Barrier Reef, across monsoonal seasons (wet and dry) and diurnal periods (morning, afternoon and night for C . singaporensis ) to quantify Sponge Associated Biota (SAB). A total of 8489 SAB was sorted from 77 sponges. Twenty‐six taxa, across 3 kingdoms and 12 phyla were recorded. Sponge‐associated biota was dominated by Mollusca in all three sponge hosts (range ~ 46%–50%) but taxa were found from a number of other phyla including, Arthropoda, Annelida, Echinodermata, Cnidaria, Foraminifera and Nemertea. There was no effect of season on abundances of SAB within the three species of sponge, but there was a significant effect associated with sponge host species, driven by a higher number of SAB in C . singaporensis and I . microconulosa . The diurnal patterns of SAB within C . singaporensis showed consistent abundances of mobile invertebrate groups with molluscs, echinoderms and arthropods dominating these samples. This study also highlights the ecological role and contribution of SAB in the reef ecosystems.

Does human movement-induced airflow elevate infection risk in burn patient’s isolation ward? A validated dynamics numerical simulation approach - Huiyi Tan; Keng Yinn Wong; Mohd Hafiz Dzarfan Othman; Bemgba Bevan Nyakuma; Desmond Daniel Chin Vui Sheng; Hong Yee Kek; Wai Shin Ho; Haslenda Hashim; Meng Choung Chiong; Muhammad Afiq Zubir; Nur Haliza Abdul Wahab; Syie Luing Wong; et al. (Energy and Buildings, 2023)

Assessment of heavy metal pollution using contamination factor, pollution load index, and geoaccumulation index in Kalpani River sediments, Pakistan - Muhammad Jamal Nasir; Abdul Wahab; Tehreem Ayaz; Sardar Khan; Amir Zeb Khan; Ming Lei (Arabian Journal of Geosciences, 2023)

Health impacts from TRAPs and carbon emissions in the projected electric vehicle growth and energy generation mix scenarios in Malaysia - Soo Chen Kwan; Sazalina binti Zakaria; Mohd Faiz Ibrahim; Wan Rozita Wan Mahiyuddin; Nurzawani Md Sofwan; Muhammad Ikram A Wahab; Radin Diana R. Ahmad; Ahmad Rosly Abbas; Wei Kian Woon; Mazrura Sahani (Environmental Research, 2023)

Fluid Flow Analysis of Integrated Porous Bone Scaffold and Cancellous Bone at Different Skeletal Sites: In Silico Study - Muhammad Azfar Noordin; Mohamad Ikhwan Kori; Abdul Hadi Abdul Wahab; Ardiyansyah Syahrom; Amir Putra Md Saad (Transport in Porous Media, 2022)

Spatial green growth in China: exploring the positive role of investment in the treatment of industrial pollution - Muhammad Imran; Naveed Hayat; Muhammad Ali Saeed; Abdul Sattar; Salman Wahab (Environmental Science and Pollution Research, 2022)

Role of financial stability, technological innovation, and renewable energy in achieving sustainable development goals in BRICS countries - Salman Wahab; Muhammad Imran; Adnan Safi; Zeeshan Wahab; Dervis Kirikkaleli (Environmental Science and Pollution Research, 2022)

Microwave-Assisted Physically Cross-Linked Chitosan-Sodium Alginate Hydrogel Membrane Doped with Curcumin as a Novel Wound Healing Platform - Hassan A. Albarqi; Abdulsalam A. Alqahtani; Irfan Ullah; Nauman Rahim Khan; Hafiz Muhammad Basit; Tayyaba Iftikhar; Abdul Wahab; Muhammad Ali; Muhammad Badar (AAPS PharmSciTech, 2022)

Design, synthesis, in vitro evaluation, and docking studies on ibuprofen derived 1,3,4-oxadiazole derivatives as dual α-glucosidase and urease inhibitors - Saima Daud; Obaid-ur-Rahman Abid; Asma Sardar; Basit Ali Shah; Muhammad Rafiq; Abdul Wadood; Mehreen Ghufran; Wajid Rehman; Zain-ul-Wahab; Fatima Iftikhar; Rifhat Sultana; Habiba Daud; et al. (Medicinal Chemistry Research, 2022)

Consumer perceptions of hybrid electric vehicle adoption and the green automotive market: the Malaysian evidence - Muhammad Iskandar Hamzah; Nurul Syafiqah Tanwir; Siti Norida Wahab; Muhammad Hafiz Abd Rashid (Environment, Development and Sustainability, 2022)

Authentication of Halal and Kosher meat and meat products: Analytical approaches, current progresses and future prospects - M. A. Motalib Hossain; Syed Muhammad Kamal Uddin; Sharmin Sultana; Yasmin Abdul Wahab; Suresh Sagadevan; Mohd Rafie Johan; Md. Eaqub Ali (Critical Reviews in Food Science and Nutrition, 2022)

A new steroidal alkaloid from Fritillaria michailovskyi Fomin - Yan Wang; Muhammad Aamer; Meral Aslay; Bilge Sener; Farooq-Ahmad Khan; Atia-tul Wahab; Atta-ur Rahman; Muhammad Iqbal Choudhary (Natural Product Research, 2022)

The Transition from Arid Farming Systems to Agroforestry Systems in Pakistan: A Comparison of Monetary Returns - Ghulam Abbas; Akhter Ali; Muhammad Khan; Hafiz Zahid Mahmood; Sazali Abdul Wahab; Rafi Amir-ud-Din (Small-scale Forestry, 2021)

Biomechanical analysis of three different types of fixators for anterior cruciate ligament reconstruction via finite element method: a patient-specific study - Nur Afikah Zainal Abidin; Abdul Hadi Abdul Wahab; Rabiatul Adibah Abdul Rahim; Mohammed Rafiq Abdul Kadir; Muhammad Hanif Ramlee (Medical & Biological Engineering & Computing, 2021)

Non-obstructive monitoring of muscle fatigue for low intensity dynamic exercise with infrared thermography technique - Muhammad Faiz Md Shakhih; Nursyazana Ridzuan; Asnida Abdul Wahab; Nurul Farha Zainuddin; Laila Fadhillah Ulta Delestri; Anis Suzziani Rosslan; Mohammed Rafiq Abdul Kadir (Medical & Biological Engineering & Computing, 2021)

In vitro morpho-physiological performance and DNA stability of banana under cadmium and drought stresses - Marwa T. El-Mahdy; Dalia A. Abdel-Wahab; Muhammad Youssef (In Vitro Cellular & Developmental Biology - Plant, 2021)

Polymerase chain reaction cycle threshold value as prerequisite for reporting of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) detection - Hafizuddin Awang; Fathul Hakim Hamzah; Mohd Hanief Ahmad; Muhammad Faris Mahmood; Azmani Wahab; Kasemani Embong; Nor Azimi Yunus (Infectious Diseases, 2021)

A case–control study of determinants for COVID-19 infection based on contact tracing in Dungun district, Terengganu state of Malaysia - Hafizuddin Awang; Effah Leiylena Yaacob; Sharifah Nadira Syed Aluawi; Muhammad Faris Mahmood; Fathul Hakim Hamzah; Azmani Wahab; Norafidah Abdul Rashid; Rosmaliza Razali; Goh Soo Ning; Kasemani Embong; Nor Azimi Yunus (Infectious Diseases, 2021)

Sponges in shallow tropical and temperate reefs are important habitats for marine invertebrate biodiversity - Ying-Yueh Chin; Jane Prince; Gary Kendrick; Muhammad Azmi Abdul Wahab (Marine Biology, 2020)

Taxonomic assessment of the Malayan water shrew Chimarrogale hantu Harrison, 1958 and reclassification to the genus Crossogale - Muhammad Farhan Abd Wahab; Dharini Pathmanathan; Masaharu Motokawa; Faisal Ali Anwarali Khan; Hasmahzaiti Omar (Mammalian Biology, 2020)

Evaluation of edible bird’s nest processing plant wastewater quality: a factory case study - Siti Shahara Zulfakar; Farah Natasha Haezam; Mohd Sham Othman; Nur Faizah Abu Bakar; Muhammad Ikram A. Wahab (Arabian Journal of Geosciences, 2020)

Evidence for genetic structuring and limited dispersal ability in the Great Barrier Reef sponge Carteriospongia foliascens - Megan R. Shaffer; Heidi M. Luter; Nicole S. Webster; Muhammad A. Abdul Wahab; James J. Bell (Coral Reefs, 2020)

Citric Acid Functionalized Bougainvillea spectabilis: a Novel, Sustainable, and Cost-effective Biosorbent for Removal of Heavy Metal (Pb2+) from Waste Water - Huma Nazir; Muhammad Salman; Makshoof Athar; Umar Farooq; Abdul Wahab; Momal Akram (Water, Air, & Soil Pollution, 2019)

The diversity and distribution of mesophotic benthic invertebrates at Ningaloo Reef, Western Australia - Muhammad Azmi Abdul Wahab; Ben Radford; Jane Fromont; Andrew M. Hosie; Karen Miller; Andrew Heyward (Marine Biodiversity, 2019)

Biodiversity and spatial patterns of benthic habitat and associated demersal fish communities at two tropical submerged reef ecosystems - Muhammad Azmi Abdul Wahab; Ben Radford; Mike Cappo; Jamie Colquhoun; Marcus Stowar; Martial Depczynski; Karen Miller; Andrew Heyward (Coral Reefs, 2018)

Phytochemical composition, biological potential and enzyme inhibition activity of Scandix pecten-veneris L. - Abdul Wahab; Syed Aleem Jan; Abdur Rauf; Zia ur Rehman; Zahid Khan; Aftab Ahmed; Fatima Syed; Sher Zaman Safi; Hamayun Khan; Muhammad Imran (Journal of Zhejiang University-SCIENCE B, 2018)

Spatial-temporal variations in surface ozone over Ushuaia and the Antarctic region: observations from in situ measurements, satellite data, and global models - Mohd Shahrul Mohd Nadzir; Matthew J. Ashfold; Md Firoz Khan; Andrew D. Robinson; Conor Bolas; Mohd Talib Latif; Benjamin M. Wallis; Mohammed Iqbal Mead; Haris Hafizal Abdul Hamid; Neil R. P. Harris; Zamzam Tuah Ahmad Ramly; Goh Thian Lai; et al. (Environmental Science and Pollution Research, 2018)

Suppression of PGE2 production via disruption of MAPK phosphorylation by unsymmetrical dicarbonyl curcumin derivatives - Mohd Fadhlizil Fasihi Mohd Aluwi; Kamal Rullah; Md. Areeful Haque; Bohari M. Yamin; Waqas Ahmad; Muhammad Wahab Amjad; Sze Wei Leong; Nurul Amira Fahmizar; Juriyati Jalil; Faridah Abas; Nor Hadiani Ismail; Ibrahim Jantan; et al. (Medicinal Chemistry Research, 2017)

Photocatalytic Degradation of Pentachlorophenol Using ZnO Nanoparticles: Study of Intermediates and Toxicity - Muneer M. Ba-Abbad; Mohd S. Takriff; Muhammad Said; Abdelbaki Benamor; Mustafa S. Nasser; Abdul Wahab Mohammad (International Journal of Environmental Research, 2017)

Characterization of rainwater chemical composition after a Southeast Asia haze event: insight of transboundary pollutant transport during the northeast monsoon - Mohd Shahrul Mohd Nadzir; Chin Yik Lin; Md Firoz Khan; Mohd Talib Latif; Doreena Dominick; Haris Hafizal Abdul Hamid; Noorlin Mohamad; Khairul Nizam Abdul Maulud; Muhammad Ikram Abdul Wahab; Nurul Farahana Kamaludin; Mohamad Azwani Shah Mat Lazim (Environmental Science and Pollution Research, 2017)

Number of pegs influence focal stress distributions and micromotion in glenoid implants: a finite element study - Abdul Hadi Abdul Wahab; Mohammed Rafiq Abdul Kadir; Muhammad Noor Harun; Tunku Kamarul; Ardiyansyah Syahrom (Medical & Biological Engineering & Computing, 2017)

Benzamide sulfonamide derivatives: potent inhibitors of carbonic anhydrase-II - Muhammad Saleem; Aamer Saeed; Atia-tul-Wahab; Ajmal Khan; Sanaullah Abbasi; Waqasuddin Khan; Sher Bahadar Khan; M. Iqbal Choudhary (Medicinal Chemistry Research, 2016)

Karakorum temperature out of phase with hemispheric trends for the past five centuries - Muhammad Usama Zafar; Moinuddin Ahmed; Mukund Palat Rao; Brendan M. Buckley; Nasrullah Khan; Muhammad Wahab; Jonathan Palmer (Climate Dynamics, 2016)

A pharmacological and toxicological evaluation of Haloxylon recurvum - Abdul Wahab; Ejaz Ahmed; Sarfraz Ahmad Nawaz; Ahsan Sharif; Rizwan Ul Haq; Abdul Malik; Muhammad Iqbal Choudhary; Mohsin Raza (Natural Product Research, 2008)